2014
DOI: 10.1089/vbz.2013.1325
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia amblyommii” andR. montanensisInfection in Dogs Following Natural Exposure to Ticks

Abstract: To determine the risk of canine infection with spotted fever group (SFG) Rickettsia spp. following natural tick exposure, 10 dogs determined to be free of evidence of exposure to or infection with tick-borne disease agents were exposed to ticks via weekly walks in a wooded area in north-central Oklahoma. After each walk, dogs were examined and the number and species of ticks present were recorded. The dogs were then returned to outdoor kennels to allow the infestations and subsequent transmission of any pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 45 publications
1
40
0
1
Order By: Relevance
“…In fact, antigenic cross-reactivity among Rickettsia of different species occurs [38]. In this regard, it is important to note that several Rickettsia species may be present at one location and even in the same tick, and thus animals may be exposed to more than one species simultaneously or over time with an unknown effect on seroreactivity [6].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, antigenic cross-reactivity among Rickettsia of different species occurs [38]. In this regard, it is important to note that several Rickettsia species may be present at one location and even in the same tick, and thus animals may be exposed to more than one species simultaneously or over time with an unknown effect on seroreactivity [6].…”
Section: Discussionmentioning
confidence: 99%
“…This patient developed an afebrile rash illness four days after being bitten by a D. variabilis tick that tested positive for R. montanensis (McQuiston 2012). A study in dogs naturally exposed to A. americanum, A. maculatum, and D. variabilis ticks suggested that several SFG rickettsia species may cause infections in canines, including R. montanensis and R. amblyommii (Barrett et al 2014).…”
Section: Potential Tick-borne Bacterial Pathogensmentioning
confidence: 94%
“…Dogs were naturally infected with R. amblyommii and R. montanensis after tick exposure. 24 Clinical evaluations of patients with specific reactivities to R. amblyommii indicated that these patients commonly experienced fever, headache, and myalgia, while anemia, thrombocytopenia, rash, and the presence of eschar occurred < 50% of the time. Previously thought to be nonpathogenic, there is increasing evidence that R. amblyommii infection in humans may be symptomatic or may cause a mild illness after a tick bite.…”
Section: Discussionmentioning
confidence: 99%